Cash flow duration and the term structure of equity returns - Weber, Michael (Journal of Financial Economics, 2018)
The term structure of equity returns is downward-sloping: stocks with high cash flow duration earn 1.10% per month lower returns than short-duration stocks in the cross-section. I create a measure of cash flow duration at the firm level using balance sheet data to show this novel fact. Factor models can explain only 50% of the return differential, and the difference in returns is three times larger after periods of high investor sentiment. Analysts extrapolate from past earnings growth into the future and predict high returns for high-duration stocks following high-sentiment periods, contrary to ex-post realizations. I use institutional ownership as a proxy for short-sale constraints, and find the negative cross-sectional relationship between cash flow duration and returns is only contained within short-sale constrained stocks.